2023
DOI: 10.5812/ijpr-134338
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ziziphus Jujuba Extract Alone and Combined with Boswellia Serrata Extract on Monosodium Iodoacetate Model of Osteoarthritis in Mice

Abstract: Background: As a chronic joint condition, osteoarthritis (OA) is a common problem among older people. Pain, aching, stiffness, swelling, decreased flexibility, reduced function, and disability are the symptoms of arthritis. Objectives: In this study, we tested the extracts of Ziziphus jujuba (ZJE) and Boswellia serrata (BSE) to reduce OA symptoms as an alternative treatment. Methods: NMRI mice were administered an intra-articular injection of monosodium iodoacetate (MIA; 1 mg/10 mL) in the left knee joint cavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Kimmatkar and colleagues, in their 2003 RCT, found that when compared with placebo controls, Boswellia extract was significant in decreasing knee pain and swelling [344]. This was also reflected in later studies, either in novel formulations or in combination with other extracts [345][346][347][348]. Neither of these studies, however, compared the efficacy of the extract with any common NSAID; hence, the results cannot be considered conclusive.…”
Section: Boswellia Serratamentioning
confidence: 99%
“…Kimmatkar and colleagues, in their 2003 RCT, found that when compared with placebo controls, Boswellia extract was significant in decreasing knee pain and swelling [344]. This was also reflected in later studies, either in novel formulations or in combination with other extracts [345][346][347][348]. Neither of these studies, however, compared the efficacy of the extract with any common NSAID; hence, the results cannot be considered conclusive.…”
Section: Boswellia Serratamentioning
confidence: 99%